Новый вид морских рыбьих пиявок crangonobdella maculosa sp. N. (hirudinea, piscicolidae) из татарского пролива и прибрежных вод Курильских островов - Утевский, C.Ю. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
Описан новый вид морских рыбьих пиявок из Северной Пацифики. Эта пиявка откладывает коконы на ракообразных Paralithodes camtschatica, Lithodes aequispina и Chionoecetes opilio, однако питается кровью рыб. Crangonobdella maculosa S. Utevsky, sp. n. близок к Crangonobdella fabricii (Malm, 1863), но отличается от него по следующим признакам: у нового вида сегментальные полоски образованы отдельными пятнами, проводящая ткань слабо развита, влагалище снабжено железистым органом. A new species of marine fish leeches from the North Pacific is described. This leech deposits its cocoons on the crustaceans Paralithodes camtschatica, Lithodes aequispina, and Chionoecetes opilio, but feeds on the fish blood. Crangonobdella maculosa S. Utevsky, sp. n. is related to Crangonobdella fabricii (Malm, 1863), but differs in the following characters: in the new species, segmental bands consist of separate spots; the conductive tissue is weakly developed; the vagina is provided with a glandular organ.